Research progress of traditional Chinese medicine as sensitizer in reversing chemoresistance of colorectal cancer - Lin, Xiang; Yang, Xinyu; Yang, Yushang; Zhang, Hangbin; Huang, Xuan (Frontiers in Oncology, 2023)
In recent years, the incidences and mortalities from colorectal cancer (CRC) have been increasing; therefore, there is an urgent need to discover newer drugs that enhance drug sensitivity and reverse drug tolerance in CRC treatment. With this view, the current study focuses on understanding the mechanism of CRC chemoresistance to the drug as well as exploring the potential of different traditional Chinese medicine (TCM) in restoring the sensitivity of CRC to chemotherapeutic drugs. Moreover, the mechanism involved in restoring sensitivity, such as by acting on the target of traditional chemical drugs, assisting drug activation, increasing intracellular accumulation of anticancer drugs, improving tumor microenvironment, relieving immunosuppression, and erasing reversible modification like methylation, have been thoroughly discussed. Furthermore, the effect of TCM along with anticancer drugs in reducing toxicity, increasing efficiency, mediating new ways of cell death, and effectively blocking the drug resistance mechanism has been studied. We aimed to explore the potential of TCM as a sensitizer of anti-CRC drugs for the development of a new natural, less-toxic, and highly effective sensitizer to CRC chemoresistance.